Personality and athletic performance: A study of Indonesian U-17 football players - Rizal Kurniawan; Amin Akbar; Rahmah Rezki Elvika; Fauziah Taslim; Maya Yasmin; Yolivia Irna Aviani; Armaita Armaita; Nurmina Nurmina (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Football players should be trained from a young age. However, to continue to develop well, many factors play a role before they become mature. One important factor is personality. This study aims to determine what personality should be possessed by grassroots-level football players in Indonesia. This study uses a qualitative method with grounded theory analysis. The primary data sources for this study are ten grassroots-level football coaches from Indonesia who have trained for five years and have a coaching license. In addition, the results of observations and documents are also additional data sources. At the data analysis stage, the researcher used open coding followed by axial and selective coding to obtain themes in this study. To help facilitate organizing and analyzing data, the researcher used Nvivo version 14. The results of this study indicate that there are five essential personalities for a grassroots-level football athlete to have, namely: Mental toughness, a trait characterized by positive, realistic, calm, and clear thinking even under pressure in a match; adaptive, namely the extent to which an athlete can adapt both in life and in a match; energetic, the extent to which an athlete has great energy to do training and matches; humble is a trait that is not arrogant and selfish in interacting with relations; and brave is a trait of daring to play every match. The results of this study can be a reference for football coaches at the grassroots level in Indonesia to improve the quality of young football players. It is hoped that further research can conduct exploratory research on personality in this study with other variables.